2023
DOI: 10.1177/15248399231175843
|View full text |Cite
|
Sign up to set email alerts
|

Remote Evidence-Based Health Promotion Programs During COVID: A National Evaluation of Reach and Implementation for Older Adult Health Equity

Abstract: Introduction. Evidence-based health promotion programs (EBPs) support older adults where they live, work, pray, play, and age. COVID-19 placed a disproportionate burden on this population, especially those with chronic conditions. In-person EBPs shifted to remote delivery via video-conferencing, phone, and mail during the pandemic, creating opportunities and challenges for older adult health equity. Method. In 2021–2022, we conducted a process evaluation of remote EBPs by purposively sampling diverse U.S. orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…MSU Extension found that entities whose mission is to serve high-need populations were often able to help recruit CDSMP participants from disparate groups. Our experience is in line with research that examined evidence-based programs implemented by 107 organizations to determine whether remote delivery could assist with reaching underserved populations (Steinman et al, 2023). We found that, as they described, working through diverse, trusted partners to implement programs in a variety of delivery formats assisted with increasing program participation and reaching underserved populations.…”
Section: Themes and Lessons Learned From Cdsmp Delivery Theme/lesson ...supporting
confidence: 81%
See 2 more Smart Citations
“…MSU Extension found that entities whose mission is to serve high-need populations were often able to help recruit CDSMP participants from disparate groups. Our experience is in line with research that examined evidence-based programs implemented by 107 organizations to determine whether remote delivery could assist with reaching underserved populations (Steinman et al, 2023). We found that, as they described, working through diverse, trusted partners to implement programs in a variety of delivery formats assisted with increasing program participation and reaching underserved populations.…”
Section: Themes and Lessons Learned From Cdsmp Delivery Theme/lesson ...supporting
confidence: 81%
“…In-person workshops resumed after the pandemic; however, some people were unable or unwilling to attend the in-person classes for a variety of reasons (e.g., transportation problems, busy schedules, the physical and psychological pain and stress of leaving the home to attend a class, lack of CDSMP availability in rural areas; Steinman et al, 2023). Participants indicated that maintaining a variety of delivery methods would better meet their needs and make it easier for them to join, and our program effectiveness data indicate that our varied delivery methods continued to meet participants' needs.…”
Section: Theme/lesson 2: Use a Combination Of Electronic And In-perso...mentioning
confidence: 99%
See 1 more Smart Citation
“…These shifts are unsurprising given the nature of program format, wherein some programs (e.g., Chronic Disease Self-Management Program) were often delivered in-person to groups of participants and others (e.g., HomeMeds) were delivered one-on-one or virtual ( 12 ). It should be noted that the COVID-19 pandemic led to innovations in program formatting (e.g., shifting to virtual models) ( 17 ). However, creating uniform data collection methods often lags behind changes in program implementation, and data reflecting program format were not consistently reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, evaluation of recent data can help illustrate the impact of the COVID-19 pandemic on the implementation of these programs. Early in the pandemic, community programming was suspended, but as the pandemic progressed the use of remote delivery options, such as video-conferencing, phone and mail, were implemented for some but not all programs ( 17 ). The return to in-person program delivery varied greatly by state and type of site.…”
Section: Introductionmentioning
confidence: 99%